ESTIMASI PARAMETER TURBULENSI UNTUK JASA PENERBANGAN BERBASIS HASIL ANALISIS BEBERAPA DATA RADIOSONDE DI KAWASAN BARAT INDONESIA - Eddy Hermawan; Zainal Abidin (Lembaga Penerbangan dan Antariksa Nasional, 2006)
The one of an important thing related to the aviation is the correct information of aviation meteorology, especially about bad weather condition such as turbulence that often disturb the plane during their flight. There are many parameters to estimate the turbulence parameter. One of them is called the Richardson Number (Ri) such as already investigated by Waco (1970). We continued hos study by applying the radiosonde data distributed at five stations in the Western part of Indonesia region, especially during the Coupling Processes Equatorial Atmoephere I (CPEA I) Campaign started from April 10 to May 10, 2004. We defined the turbulence when Ri less more 0.25 as described by Killer (1981). We found initial turbulence occurrence indication, even though we have found significant indication yet, related with less of locations and data observations which is only one month observation. Turbulance in the plane is described as the changes of vertical gravitation in the plane and observed by vertical accelerometer which is installed in the plane. After making some validations with the vertical accelerometer data, we found only a few good correlation between Ri and turbulence. We suspect it caused by the less of data observation. But initial indication based on data analysis shows that light turbulence occurrence a long Eastern Coast of Malacca Peninsula on 19th April 2004.